Efektivitas Strategi Pembelajaran REACT (Relating, Experiencing, Applying, Cooperating, Transfering) terhadap Hasil Belajar Matematika pada Mahasiswa Pendidikan Matematika - Suaedy, Nurdyanti (Lembaga Yasin AlSys, 2024)
Background: The 2022 PISA report reveals that the average mathematics score of Indonesian students was 366, significantly below the OECD average of 472. In addressing the global demand for critical thinking, collaboration, and practical application skills, traditional teaching approaches that focus solely on information dissemination are no longer sufficient. Consequently, new learning strategies, such as the REACT (Relating, Experiencing, Applying, Cooperating) approach, are necessary to bridge theory and practice. Method: The researchers employed a quantitative approach with a quasi-experimental design. The study sample consisted of Class A students, selected using a cluster sampling technique. Data collection methods included tests and observation sheets. The test instrument assessed problem-solving abilities through pre-tests and post-tests, while observation sheets monitored mathematics learning activities. The instruments were analysed descriptively (student activity sheets and learning outcomes) and inferentially (examining differences between pre-test and post-test scores). Results: Descriptive statistics showed that the mean pre-test score was 72.28, which increased to 87.08 in the post-test. Furthermore, the gain classification indicated that most students (23 individuals) fell into the moderate category, with two students in the low category. The Wilcoxon statistical test confirmed a significant difference in average mathematics learning outcomes. Conclusion: The analysis results indicated a significant improvement in student learning outcomes with the REACT learning strategy. The students’ average post-test scores increased significantly compared to their pre-test scores, supported by statistical tests demonstrating meaningful differences through both descriptive and inferential analyses.